The accuracy of portable peak flow meters. - Miller, M R (1992)
BACKGROUND: The variability of peak expiratory flow (PEF) is now commonly used in the diagnosis and management of asthma. It is essential for PEF meters to have a linear response in order to obtain an unbiased measurement of PEF variability. As the accuracy and linearity of portable PEF meters have not been rigorously tested in recent years this aspect of their performance has been investigated. METHODS: The response of several portable PEF meters was tested with absolute standards of flow generated by a computer driven, servo controlled pump and their response was compared with that of a pneumotachograph. RESULTS: For each device tested the readings were highly repeatable to within the limits of accuracy with which the pointer position can be assessed by eye. The between instrument variation in reading for six identical devices expressed as a 95% confidence limit was, on average across the range of flows, +/- 8.5 l/min for the Mini-Wright, +/- 7.9 l/min for the Vitalograph, and +/- 6.4 l/min for the Ferraris. PEF meters based on the Wright meter all had similar error profiles with overreading of up to 80 l/min in the mid flow range from 300 to 500 l/min. This overreading was greatest for the Mini-Wright and Ferraris devices, and less so for the original Wright and Vitalograph meters. A Micro-Medical Turbine meter was accurate up to 400 l/min and then began to underread by up to 60 l/min at 720 l/min. For the low range devices the Vitalograph device was accurate to within 10 l/min up to 200 l/min, with the Mini-Wright overreading by up to 30 l/min above 150 l/min. CONCLUSION: Although the Mini-Wright, Ferraris, and Vitalograph meters gave remarkably repeatable results their error profiles for the full range meters will lead to important errors in recording PEF variability. This may lead to incorrect diagnosis and bias in implementing strategies of asthma treatment based on PEF measurement.